Risk factors, incidence and persistence of symptoms from the eyes among professional computer users. - Toomingas, A.; Hagberg, M.; Heiden, M.; Richter, H.; Westergren, K.E.; Tornqvist, E. Wigaeus (Work, 2014)
BACKGROUND: Symptoms from the eyes are common among computer users. Knowledge is scarce about these problems, however. OBJECTIVES: The aim was to study risk-factors, incidence and persistence of eye-symptoms among professionally active computer users. METHODS: This was a questionnaire based prospective study where 1283 males and females from different professions and companies answered a baseline questionnaire about individual factors and working conditions, e.g. duration of daily computer work, comfort of screen work, psychosocial factors. Subjects were at baseline and 10 follow-ups asked about the number of days with eye-symptoms during the preceding month. RESULTS: The incidence-rate of symptoms persisting minimum three days was 0.38/person-year. A multivariate Hazard-ratio model showed significant associations with extended continuous computer work, tasks with high demands on eye-hand coordination, low level of control, visual discomfort, female sex and nicotine use. Eye-symptoms at baseline was a strong risk factor for new symptoms. CONCLUSION: The incidence of eye-symptoms among professional computer users is high and related to both individual and work-related factors. The organization of computer work should secure frequent breaks from near-work at the computer screen. The severity of vision-related problems could in field studies be quantified by asking for the persistence of symptoms.